2020
DOI: 10.1186/s13018-020-01942-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the pronator quadratus repair following volar plating of distal radius fractures

Abstract: Background Distal radius fracture (DRF) is the most common upper extremity fracture that requires surgery. Operative treatment with a volar locking plate has proved to be the treatment of choice for unstable fractures. However, no consensus has been reached about the benefits of pronator quadratus (PQ) repair after volar plate fixation of DRF in terms of patient-reported outcome measures, pronation strength, and wrist mobility. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
10
1
1
Order By: Relevance
“…Fenglei Shi concluded in a study that whether or not to repair the PQ muscle may not improve late wrist function in patients [ 18 ]. However, Chun-Kuan Lu suggested that repairing the PQ muscle may have some effects on pronation strength, and it is uncertain whether repairing the PQ is a protective factor in preventing flexor tendon complications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenglei Shi concluded in a study that whether or not to repair the PQ muscle may not improve late wrist function in patients [ 18 ]. However, Chun-Kuan Lu suggested that repairing the PQ muscle may have some effects on pronation strength, and it is uncertain whether repairing the PQ is a protective factor in preventing flexor tendon complications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there was no statistical difference in wrist function between the repair group and the non-repair group was found in their study. Lu et al performed a meta-analysis and found that PQ muscle repair showed different effects on pronation strength in different groups (32).We conducted a subgroup analysis by the length of follow-up time and the results showed that the significant difference in pronation angle between the two groupsafter short-term and long-term follow-up. Both previous articles included some retrospective studies, and the level of evidence Risk of bias summary: review authors' judgments about each risk of bias item for each included study.…”
Section: Discussionmentioning
confidence: 88%
“…Flexor tendinitis including tendon rupture is a possible complication. Lu et al [33] advocated that repair of PQ muscle might have a slight effect on pronation function, but it was not certain whether repair of pronator muscle was a protective factor to prevent exor tendon complications. Most clinicians believed that plate placement and PQ muscle maintenance played a signi cant role in prevention.…”
Section: Discussionmentioning
confidence: 99%